Photolytic radical persistence due to anoxia in viscous aerosol particles - Peter A. Alpert (Nature Portfolio, 2021)
Sunlight can change the composition of atmospheric aerosol particles, but the mechanisms through which this happens are not well known. Here, the authors show that fast radical reaction and slow diffusion near viscous organic particle surfaces can cause oxygen depletion, radical trapping and humidity dependent oxidation.